CREATIVE STRATEGY IN PRODUCTION OF PROMOTION VIDEO FOR THE RATTAN TOURISM VILLAGE OF TRANGSAN - Morgana, Daniel Andhika; Rizal H, Sigit; Bilankawa, Firdana; Ramadhian, Alpin; Ardi Candra D.A, Nur Rahmat (Seni Media Rekam ISI Surakarta, 2019)
One aspect that affects the speed of development of a tourist village is the promotion of the village. Promotion of village tourism is very important especially for villages that are pioneering. Village promotion can be carried out by internal elements who carry out promotions and information intensively. Therefore, it is necessary to involve the village youth group